MEME POLITIK SETYA NOVANTO SEBAGAI REPRESENTASI DEMOKRASI DIGITAL DI INDONESIA: ANALISIS WACANA KRITIS - Andriani, Viena Wanidha (Adabiyyāt: Jurnal Bahasa dan Sastra, 2019)
Political memes of Setya Novanto (Setnov) are assumed to have constructed critical ideological discourses that reflect the digital democracy in Indonesia. The courage of social media users to strongly criticize the political elite is very interesting to be analyzed. By using Fairclough’s Critical Discourse Analysis (CDA), this article examines how social media memes construct the discourse on Setya Novanto, which ideology is conveyed through the memes, and to whom it is addressed. Also, this study analyzes the socio-ccultural context as the background of these memes. The result of the analysis shows that the political memes of Setya Novanto construct a negative image of him and the people involved in his case. Based on the analysis of the discursive practices, it is found that the ideology is addressed to the government and the people related to the case. Meanwhile, the public response indicates that the distribution of the ideology is both received and supported by the audience. Based on the sociocultural analysis, it is understood that systematic corruption, low public trust to the political elite and government, and the flexibility of online media become the key factors to the emergence of the memes.